(untitled) (Journal of the College of Education for Women, 2019)
This study presents certain modifications done to the conditions set by Searle(1969: 57) concerning the speech act of promising in order to render them to selectedsayings of Prophet Muhammad (P.B.U.H.) and Jesus Christ (P.B.U.H.) and topolitical texts. These modifications make the conditions of the speech act ofpromising appropriate for sincere promises made by the Messengers of God sincethey deliver their Messages of God but they are unable, as Messengers, to fulfillGod’s promises which they make as part of their Messages and by representatives ofStates who deliver speeches on behalf of their Governments. These are the only twosituations where the speakers can make promises and do not fulfill these promises bythemselves according to Searle’s conditions of speech act of promising. This is anattempt to fill a gap in Searle’s speech act theory.